Effect of Anesthesia on Oligodendrocyte Development in the Brain - Fu, Ningning; Zhu, Ruilou; Zeng, Shuang; Li, Ningning; Zhang, Jiaqiang (Frontiers in Systems Neuroscience, 2022)
Oligodendrocytes (OLs) participate in the formation of myelin, promoting the propagation of action potentials, and disruption of their proliferation and differentiation leads to central nervous system (CNS) damage. As surgical techniques have advanced, there is an increasing number of children who undergo multiple procedures early in life, and recent experiments have demonstrated effects on brain development after a single or multiple anesthetics. An increasing number of clinical studies showing the effects of anesthetic drugs on the development of the nervous system may mainly reside in the connections between neurons, where myelin development will receive more research attention. In this article, we review the relationship between anesthesia exposure and the brain and OLs, provide new insights into the development of the relationship between anesthesia exposure and OLs, and provide a theoretical basis for clinical prevention of neurodevelopmental risks of general anesthesia drugs.